(a^2-x^2)^{n-(1/2)}[0,a]などの定積分

\begin{alignat}{2}
&(1)  \displaystyle\int_0^{\infty} \frac{1}{(x^2+a^2)^n}dx=\frac{π}{2a^{2n-1}}\cdot \frac{(2n-3)!!}{(2n-2)!!}\\
&(2)  \displaystyle\int_0^a (a^2-x^2)^{n-\frac{1}{2}}dx=\frac{πa^{2n}}{2}\cdot \frac{(2n-1)!!}{(2n)!!}\\
\end{alignat}ただし、全て \(n \in \mathrm{N}\)






<証明>

\((1)\) \(x^2=a^2t\) と置きます。\((2xdx=a^2dt)\)$$\displaystyle\int_0^{\infty} \frac{1}{(x^2+a^2)^n}dx=\displaystyle\int_0^{\infty} \frac{1}{(a^2t+a^2)^n} \cdot \frac{a}{2\sqrt{t}}dt=\frac{1}{2a^{2n-1}}\displaystyle\int_0^{\infty} \frac{1}{(t+1)^n \sqrt{t}}dt $$\((t+1=s)\) と置きます。\((dt=ds)\)$$=\frac{1}{2a^{2n-1}}\displaystyle\int_1^{\infty} \frac{1}{s^n\sqrt{s-1}}ds$$\(\displaystyle s=\frac{1}{r}\) と置きます。\(\displaystyle \left(dr=-\frac{1}{r^2dr}\right)\)
\begin{alignat}{2}
&=\frac{1}{2a^{2n-1}}\displaystyle\int_1^0 \frac{r^n}{\sqrt{\frac{1}{r}-1}}\left(-\frac{1}{r^2}\right)dr\\
&=\frac{1}{2a^{2n-1}}\displaystyle\int_0^1 r^{n-\frac{3}{2}}(1-r)^{-\frac{1}{2}}dr\\
&=\frac{1}{2a^{2n-1}}B\left(n-\frac{1}{2},\frac{1}{2}\right)\\
&=\frac{1}{2a^{2n-1}} \cdot \frac{Γ\left(n-\frac{1}{2}\right)Γ\left(\frac{1}{2}\right)}{Γ(n)}\\
&=\frac{\sqrt{π}}{2a^{2n-1}}\cdot \frac{Γ\left(n+\frac{1}{2}\right)}{n-\frac{1}{2}} \cdot \frac{1}{Γ(n)}\\
&=\frac{\sqrt{π}}{2a^{2n-1}} \cdot \frac{1}{2n-1} \cdot \frac{(2n-1)!!}{2^{n-1}}\sqrt{π}\cdot \frac{1}{(n-1)!}\\
&=\frac{π}{2a^{2n-1}}\cdot \frac{(2n-3)!!}{2^{n-1} \cdot (n-1)!}=\frac{π}{2a^{2n-1}}\cdot \frac{(2n-3)!!}{(2n-2)!!}
\end{alignat}以上より$$\displaystyle\int_0^{\infty} \frac{1}{(x^2+a^2)^n}dx=\frac{π}{2a^{2n-1}}\cdot \frac{(2n-3)!!}{(2n-2)!!}$$







\((2)\) \(x=at\) と置きます。\((dx=adt)\)$$\displaystyle\int_0^a (a^2-x^2)^{n-\frac{1}{2}}dx=\displaystyle\int_0^1 (a^2-a^2t^2)^{n-\frac{1}{2}} \cdot adt=a^{2n}\displaystyle\int_0^1 (1-t^2)^{n-\frac{1}{2}}dt$$\(t^2=s\) と置きます。\((2tdt=ds)\)
\begin{alignat}{2}
&=a^{2n}\displaystyle\int_0^1 (1-s)^{n-\frac{1}{2}} \cdot \frac{1}{2\sqrt{s}}ds=\frac{a^{2n}}{2}\displaystyle\int_0^1 (1-s)^{n-\frac{1}{2}} s^{-\frac{1}{2}}ds\\
&=\frac{a^{2n}}{2}B\left(n+\frac{1}{2},\frac{1}{2}\right)=\frac{a^{2n}}{2}\cdot \frac{Γ\left(n+\frac{1}{2}\right)Γ\left(\frac{1}{2}\right)}{Γ(n+1)}\\
&=\frac{a^{2n}}{2} \cdot \frac{(2n-1)!!}{2^n}\sqrt{π} \cdot \frac{\sqrt{π}}{n!}=\frac{πa^{2n}}{2}\cdot \frac{(2n-1)!!}{(2n)!!}
\end{alignat}以上より$$\displaystyle\int_0^a (a^2-x^2)^{n-\frac{1}{2}}dx=\frac{πa^{2n}}{2}\cdot \frac{(2n-1)!!}{(2n)!!}$$

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です